Development of Mini-Conveyor Trainer Kit based on Modbus Protocol - Nari, M I; Purnomo, Fendik; Kautsar, S; Rofi'i, A; Winardi, A W; Afianah, N; Putri, S L (International Journal of Technology, Food and Agriculture, 2025)
This research focuses on the development of a Mini-Conveyor Trainer Kit designed for automation system education. The prevalent communication protocol in the industry is the Modbus protocol. Therefore, the mini conveyor controller is equipped with an RS485 module to enable communication via the Modbus protocol. The mini conveyor employs a DC motor and is controlled using an 8-bit microcontroller. By utilizing the Modbus protocol, the mini conveyor can be controlled through a PLC, simulating an industrial conveyor system. This approach provides a comprehensive understanding of automation systems to learners. The trainer kit aims to bridge the gap between theoretical knowledge and practical application in automation systems. The integration of the Modbus protocol allows for real-time control and monitoring, which are critical skills in modern industrial settings. Throughout this research, we detail the design and implementation process of the mini conveyor system, including hardware setup, microcontroller programming, and Modbus communication protocol configuration. Additionally, we conduct a series of tests to evaluate the system's performance, reliability, and response time when controlled via a PLC. The results demonstrate that the mini conveyor trainer kit successfully replicates the functionality of industrial conveyor systems, making it an invaluable tool for educational purposes. Learners can gain hands-on experience with industrial communication protocols and control systems, enhancing their understanding and preparedness for careers in automation and manufacturing industries. In conclusion, the development of this Mini-Conveyor Trainer Kit provides an effective educational tool that aligns with industry standards, thereby enriching the learning experience and equipping students with essential skills for the future.